Staphylococcus aureus binding to Seraph® 100 Microbind® Affinity Filter: Effects of surface protein expression and treatment duration. - Malin-Theres Seffer; Martin Weinert; Gabriella Molinari; Manfred Rohde; Lothar Gröbe; Jan T Kielstein; Susanne Engelmann (PLoS ONE, 2023)
Introduction Extracorporeal blood purification systems represent a promising alternative for treatment of blood stream infections with multiresistant bacteria. Objectives The aim of this study was to analyse the binding activity of S. aureus to Seraph affinity filters based on heparin coated beads and to identify effectors influencing this binding activity. Results To test the binding activity, we used gfp-expressing S. aureus Newman strains inoculated either in 0.9% NaCl or in blood plasma and determined the number of unbound bacteria by FACS analyses after passing through Seraph affinity filters. The binding activity of S. aureus was clearly impaired in human plasma: while a percent removal of 42% was observed in 0.9% NaCl (p-value 0.0472) using Seraph mini columns, a percent removal of only 10% was achieved in human plasma (p-value 0.0934). The different composition of surface proteins in S. aureus caused by the loss of SarA, SigB, Lgt, and SaeS had no significant influence on its binding activity. In a clinically relevant approach using the Seraph® 100 Microbind® Affinity Filter and 1000 ml of human blood plasma from four different donors, the duration of treatment was shown to have a critical effect on the rate of bacterial reduction. Within the first four hours, the number of bacteria decreased continuously and the reduction in bacteria reached statistical significance after two hours of treatment (percentage reduction 64%, p-value 0.01165). The final reduction after four hours of treatment was close to 90% and is dependent on donor. The capacity of Seraph® 100 for S. aureus in human plasma was approximately 5 x 108 cells. Conclusions The Seraph affinity filter, based on heparin-coated beads, is a highly efficient method for reducing S. aureus in human blood plasma, with efficiency dependent on blood plasma composition and treatment duration.